Neuroprotective properties of curcumin in toxin-base animal models of Parkinson's disease: a systematic experiment literatures review - Xin-Shi Wang; Zeng-Rui Zhang; Man-Man Zhang; Miao-Xuan Sun; Wen-Wen Wang; Cheng-Long Xie (BMC, 2017)
Abstract Background Curcumin (diferuloylmethane), a polyphenol extracted from the plant Curcuma longa, is widely used in Southeast Asia, China and India in food preparation and for medicinal purposes. Meanwhile, the neuroprotective actions of curcumin have been documented for experimental therapy in Parkinson's disease (PD). Methods In this study, we used a systematic review to comprehensively assess the efficacy of curcumin in experimental PD. Using electronic and manual search for the literatures, we identified studies describing the efficacy of curcumin in animal models of PD. Results We identified 13 studies with a total of 298 animals describing the efficacy of curcumin in animal models of PD. The methodological quality of all preclinical trials is ranged from 2 to 5. The majority of the experiment studies demonstrated that curcumin was more significantly neuroprotection effective than control groups for treating PD. Among them, five studies indicated that curcumin had an anti-inflammatory effect in the PD animal models (p < 0.05). Meanwhile, four studies showed the antioxidant capability of curcumin, by which it protected substantia nigra neurons and improved striatal dopamine levels. Furthermore, two studies in this review displayed that curcumin treatment was also effective in reducing neuronal apoptosis and improving functional outcome in animal models of PD. Most of the preclinical studies demonstrated the positive findings while one study reported that curcumin had no beneficial effects against Mn-induced disruption of hippocampal metal and neurotransmitter homeostasis. Conclusions The results demonstrated a marked efficacy of curcumin in experimental model of PD, suggesting curcumin probably a candidate neuroprotective drug for human PD patients.